Efeitos de dominância linguística e de tempo de exposição formal à língua na produção de pronomes clíticos por crianças bilingues português/francês - Tomaz, Margarida; Lobo, Maria; Madeira, Ana; Soares-Jesel, Carla; Vaz, Stéphanie (Revista da Associação Portuguesa de Linguística, 2020)
This study investigates the effects of two external linguistic variables – language dominance and time of formal exposure – on the production and placement of clitic pronouns of Portuguese-French bilingual children. Using two elicited production tasks and a parental sociolinguistic questionnaire, we show that language dominance plays a role in rates of omission and rates of clitic production. On the other hand, a higher time of formal exposure to Portuguese does not determine better performance neither in what concerns clitic omission nor clitic placement in Portuguese-French bilingual children.